The role of the National bank of Ukraine in ensuring the stable development of the banking system - Pohorelenko , N. P. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
Based on the analysis of the problems that occurred during the escalation of the systemic crisis in Ukraine, the work analyzes the activities of the National Bank of Ukraine in the context of "resetting" the regulatory function and enhancing its institutional capacity to ensure the financial stability of the domestic banking system on the basis of available tools. The National Bank of Ukraine, in accordance with the current Law, within the limits of its powers, contributes to financial stability, including the stability of the banking system, provided that it does not discourage the achievement of price stability. Therefore, NBU pays much attention to the state of the financial system in general and to the analysis and opposition of risks that could disrupt its sustainability. It has been determined that the regulator has started the conceptual changes which have been analyzed in detail: revision of the approaches to the components of macro-prudential policy instruments; move to banking supervision based on clustering with the help of grouping for the purposes of supervising banks with similar business models (their transparency and risk), risk profiles, the sense of operations or other features; changes in approaches to stress testing (in order to define the "weaknesses" of banking regulation and prudential supervision). The considered changes represent not only the transformation of its regulatory function. First of all, it is an increase of its institutional capacity by optimizing its activity as a modern mobile regulator, ready for new challenges in rapidly changing conditions.